MULTIMODALITAS YANG MENGKONSTRUKSI HUMOR DAN TEKS TERJEMAHAN TAKARIR YANG MENGANDUNG UNSUR BUDAYA SPESIFIK PADA SERIAL KOMEDI - Ilham, Ilham; Verawati, Verawati; Arnisyah, Siti; Perdana, Indra (Universitas Hamzanwadi, 2024)
This study aims to analyze: (1) the multimodality system in constructing humor in the comedy series Malam Minggu Miko 2 and (2) the translation techniques applied to the subtitles of the series, with a particular focus on Culture-specific items. A qualitative descriptive method was employed to capture and analyze data from Malam Minggu Miko 2. The primary data comprised scenes containing cultural elements in the series' subtitles, while secondary data included additional relevant information supporting the study. The findings reveal that 36 scenes contained Culture-specific items, 14 of which were classified into specific domains such as character names, gimmicks, and food names. This study contributes by demonstrating how multimodal systems provide a comprehensive understanding of humor construction and the translation of Culture-specific items in Audio-Visual Translation (AVT). Furthermore, it offers new insights into the interplay between visual and textual elements in translation studies.